Geometric Zeta-Function and Euclidean Action - Javtokas, A. (Nonlinear Analysis: Modelling and Control, 2003)
This paper provides analysis on successful combining Euclidean action and geometric zeta-function, investigating distribution of the zetafunction poles (spectrum).
Keywords: geometric zeta-function; Euclidean action; complex dimensions; zeta-function poles